Integrated geophysical and hydromechanical assessment for CO2 storage: shallow low permeable reservoir sandstones. (July 2016) - Falcon‐Suarez, Ismael; North, Laurence; Amalokwu, Kelvin; Best, Angus
ABSTRACT: Geological reservoirs can be structurally complex and can respond to CO2 injection both geochemically and geomechanically. Hence, predicting reservoir formation behaviour in response to CO2 injection and assessing the resulting hazards are important prerequisites for safe geological CO2 storage. This requires a detailed study of thermal‐hydro‐mechanical‐chemical coupled phenomena that can be triggered in the reservoir formation, most readily achieved through laboratory simulations of CO2 injection into typical reservoir formations. Here, we present the first results from a new experimental apparatus of a steady‐state drainage flooding test conducted through a synthetic sandstone sample, simulating real CO2 storage reservoir conditions in a shallow (∼1 km), low permeability ∼1mD, 26% porosity sandstone formation. The injected pore fluid comprised brine with CO2 saturation increasing in steps of 20% brine/CO2 partial flow rates up to 100% CO2 flow. At each pore fluid stage, an unload/loading cycle of effective pressure was imposed to study the response of the rock under different geomechanical scenarios. The monitoring included axial strains and relative permeability in a continuous mode (hydromechanical assessment), and related geophysical signatures (ultrasonic P‐wave and S‐wave velocities Vp and Vs, and attenuations Qp −1 and Qs −1, respectively, and electrical resistivity). On average, the results showed Vp and Vs dropped ∼7% and ∼4% respectively during the test, whereas Qp −1 increased ∼55% and Qs −1 decreased by ∼25%. From the electrical resistivity data, we estimated a maximum CO2 saturation of ∼0.5, whereas relative permeability curves were adjusted for both fluids. Comparing the experimental results to theoretical predictions, we found that Gassmann's equations explain Vp at high and very low CO2 saturations, whereas bulk modulus yields results consistent with White and Dutta–Odé model predictions. This is interpreted as a heterogeneous distribution of the two pore fluid phases, corroborated by electrical resistivity tomography images. The integration of laboratory geophysical and hydromechanical observations on representative shallow low‐permeable sandstone reservoir allowed us to distinguish between pure geomechanical responses and those associated with the pore fluid distribution. This is a key aspect in understanding CO2 injection effects in deep geological reservoirs associated with carbon capture and storage practices.